Extra small metacentric chromosome identified as i(18p). - Rocchi, M (1979)
A case of a supernumerary metacentric small chromosome, diagnosed at birth, is described. The cytogenetic findings support its identification as i(18p). The clinical development from birth to 12 months is reported, with particular attention given to the psychomotor retardation and to the immunological aspect.